Real-time interactive spatial augmented reality (RISAR) platform - Chan, Aye Zay Hta (2022)
Spatial Augmented Reality (SAR) is a unique type of Augmented Reality technology where virtual and real-world objects are blended together by projecting virtual images onto real-world objects using projection mapping. Despite the presence of various SAR platforms, most of them rely on pre-built models that do not allow for dynamic modifications to the physical structure. Consequently, users are unable to change the physical structure to better express their ideas, thus limiting the interaction between the users and the platform. This can be a difficult hurdle to overcome when it comes to applications that need quick, real-time prototyping in order to accurately display the effects of any alterations made to a physical structure. Therefore, this research project aims to design and develop a tracker-based SAR platform to resolve the aforementioned challenges. The main contributions of this Real-time Interactive Spatial Augmented Reality (RISAR) platform include (i) an algorithm that supports real-time physical structure reconstruction using Lego blocks and projection mapping, and (ii) a design of a SAR platform with low-cost and easily accessible hardware and software. The design and development of RISAR platform included three phases namely, (i) object detection, (ii) marker tracking and (iii) dynamic projection mapping. This project used prototyping methodology where five prototypes were developed in phases to achieve the objectives. The platform was then evaluated by conducting a system test and end-user usability test. The results showed that the RISAR platform was able to successfully detect the user constructed Lego object in real-time, and dynamically project out the virtual content onto the tangible Lego blocks in real-time.